Silk Mania in the Auburn Prison, 1841–44. (3rd July 2021) - Green, Denise Nicole; Breen, Nancy
Abstract : From 1841 to 1844, the Auburn Prison in New York State, now the Auburn Correctional Facility, was the location of an early experiment in the manufacture of sewing silk, a type of thread used in garment production. Incarcerated men worked in throwing mills to transform cocoons into sewing silk; they reeled, combed, and dyed silk filaments, added twist, and wound the thread onto bobbins. The Auburn Prison agent solicited cocoons from silk farmers and thereby supported an incipient local sericulture cottage industry. By 1843 the prison had become the leading buyer of raw silk cocoons in the United States. In this report, we chronicle the rise and fall of silk production in the Auburn Prison within the context of the Auburn Prison System, also known as the "Congregate System, " and a larger "silk mania" across the northeastern United States in the second quarter of the nineteenth century.